Physical and chemical characteristics of Chitofudregs nugget in comparison to commercial nugget - Siti Susanti; Bhakti Etza Setiani; Nurwantoro Nurwantoro; Ahmad Ni’matullah Al-Baarri (Institute of Advanced Engineering and Science, 2023)
The study aims to compare the physical characteristics (water holding capacity and cooking loss) and chemical characteristics (moisture, protein, fat, ash, carbohydrate content, and total calories) of Chitofudregs nugget with commercial nuggets. Four categories of nuggets which are Fiesta, So Good, Nugget Curah, and Chitofudregs nugget (FT, SG, NC, and Chitofudregs) were determined as treatments in this study with 5 repetitions for each category. The experimental method of this research was a randomized design complete (RDC). Physically, Chitofudregs had the highest water-holding capacity and the lowest cooking loss among all commercial nuggets (p<0.05) so there were not many nutrient losses during the processing. Chemically, Chitofudregs contained higher water content than one of the commercial-NC nuggets while the protein and ash content was lower than the two types of commercial nuggets (FT and SG) with carbohydrate content which was also lower than the NC commercial nuggets (p<0.05). The fat content and total calories of chitofudreg were the lowest among all commercial nuggets (p<0.05). Chitofudregs are combination nuggets whose physical quality is as good as commercial nuggets with specific chemical characteristics and has potency as a diet product because it is low in fat and calories.